ANALISIS PENGGUNAAN APBN OLEH DEWAN PERWAKILAN RAKYAT DALAM PERGANTIAN GORDEN RUMAH DINAS - Jennifer Claudia; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2022)
The House of Representatives in shortened or widely known in Indonesia as the DPR is one of theIndonesian state institutions that arranged through an election. Which selected by the peoplethrough a general election aimed at becoming the representative voice of the Indonesian people.As in listening the aspirations of the Indonesian people and voicing the voice of the peopleincluded the smallest circle in Indonesia. In the period of the Covid 19 pandemic as the Indonesianpeople are facing and going through with the impact of the pandemic there are losses in variousterms especially in terms of the country's economy. The House of Representatives (DPR) proposeda nominal budget to buy and change one of the internal needs of the House of Representatives(DPR) service house in fantastic and big nominal which is for curtains. The emergence of an eventlike this from an Indonesian state institution that is supposed to be a figure that is seen andmodeled by the Indonesian people precisely raises concern and lack of trust from the Indonesianpeople. Because it is often judged to propose or decide something without considering andthinking about welfare also justice for the people of Indonesia. In this case the Indonesian state isconsidered to spend a fantastic amount of money is a waste in an unimportant or non-emergencything. As said in the statute the invitation of Indonesia that decisions regarding the state's financessuch as from the State Revenue and Spending Budget (APBN) should be based in consideration ofjustice and welfare for the people of Indonesia.